Risk of Falls with Benzodiazepine Receptor Agonists in Combination with Novel hypnotics. - Higuchi, Yuya; Ishikawa, Yuya; Araki, Takuya; Ohshima, Yukina; Yashima, Hideaki; Yamamoto, Koujirou (Indonesian Journal of Pharmaceutics, 2023)
Several risk factors for falls during hospitalization have been reported, of which hypnotics have a major influence. Insomnia is often intractable, and many cases are treated with two or more hypnotics; however, there is concern about the increased risk of falls due to the use of multiple hypnotics. Therefore, we aimed to clarify the effects of combining conventional and new hypnotics on the risk of falls. The impact of the concomitant use of hypnotics on the occurrence of fall events was evaluated retrospectively in patients 20 years of age and older received acute care medicine in an university hospital between January 2013 and August 2022. The survey items included age, sex, drug prescription status, whether a fall accident had occurred, and its circumstances. Of the 47,236 eligible patients, 976 experienced a fall accident during hospitalization (fall rate, 2.07%). Logistic regression analysis of the patient population not taking benzodiazepine receptor agonists showed that age (odds ratio [OR], 1.04), sex (OR, 0.84), and ramelteon use (OR, 3.06) independently contributed to falls. In contrast, in the patient population taking benzodiazepine receptor agonists, logistic regression analysis showed that only age (odds ratio [OR]: 1.03) and sex (OR: 0.76) independently contributed to falls. This suggests that ramelteon, suvorexant, and lemborexant, in combination with benzodiazepines, may not increase the risk of falls. Hypnotics with novel mechanisms of action may not increase the risk of fall when combined with benzodiazepine receptor agonists.